Simulation Model in the Strategic Decision-Making Process at the Subnational Level Using the AHP Method Based on the Risk Criterion: A Continuation of Previous Research - Davor Žmegač (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In previous research, which this paper continues, a proposal was made for a possible improvement of the matrix analysis model in the function of supporting strategic decision making at the regional level. This paper introduces the Analytic Hierarchy Process (AHP) as one of the methods of multi-criteria analysis in the final part of the decision-making process where, based on defined criteria, the optimal solution is selected from a possible number of alternative solutions. Regarding the criteria for selecting alternative solutions, risk is introduced into the process as the main criterion. Based on previously established principles, a simulation model is developed, first presenting a review of recent literature with a critical review of the main modelling methods and then determining the assumptions and limitations of modelling. The final simulation model in this paper yields satisfactory results that point to the possible application of the model in solving real problems of strategic planning in the field of regional economy. The application of the AHP method in a real decision-making environment at the subnational level of the public sector and drawing attention to the importance of public sector risk management are further highlighted as a value of this research.